Deep eutectic solvents as a soil washing agent for the removal of heavy metal contaminants in mangrove soil / Shahidah Nusailah Rashid - Shahidah Nusailah , Rashid (2024)
Mangroves are coastal ecosystems that provide vital support for the survival of aquatic organisms and people. However, the size of mangroves declines every year due to environmental threats that come from natural and anthropogenic activities. Thus, it is important to conserve and remediate mangrove forests. It was reported that mangrove soil in many countries was contaminated with high heavy metal concentrations. Soil washing is one of the common remediation techniques adopted to remove contamination from soil. Deep eutectic solvents or DES could be the next promising solution to remediate nature and polluted areas from pollutant and toxic materials. Owing to their superior properties and economical, simplicity in production and biocompatibility make DES the successive green solvent. Thus, this study proposed using DES to remove heavy metals, such as Pb, As, and Ni ions, from mangrove soil. Different DESs were screened and selected using computational software, such as COnductor, like Screening MOdel for Realistic Solvents (COSMO-RS). This software was used to investigate the thermodynamic behavior of different DES towards heavy metals. Mangrove soil spiked with Pb, As, and Ni ions were washed and removed using DES selected by COSMO-RS with the highest capacity. Based on the result generated by COSMO-RS for the highest capacity, it was found that ChCl: Lactic Acid [1:2] (ChCl-LacA) and ChCl: Levulinic Acid [1:2] (ChCl-LevA) are the most potential DESs for lead removal from mangrove soil. The parametric study identified key processing parameters such as DES concentration, soil-to-liquid ratio, and contact time. The result showed that 40% of natural-based DES ( ChCl-LacA), a solid/liquid ratio of 1:15, and a contact time of 3 hours were the optimum parameters to remove lead from mangrove soil with 97% removal efficiency, while the optimum removal parameters for lead were found to be at 60% concentration of natural-based DES ( ChCl-LevA), 1:15 solid/liquid ratio and 3 hours contact time with a removal efficiency of 99%. Tetrabutylammonium chloride: Triethylene glycol [1:2] (TBAC-TEG) as chemical-based DES was able to remove arsenic with a removal efficiency of 85.42% under the following optimum operating conditions (DES concentration of 2% and 1:5 solid/liquid ratio and 3 hours contact time). ChCl: Acetic Acid [1:2] (ChCl-AceA) and ChCl: Levulinic Acid [1:2] (ChCl-LevA) could extract Ni ions from contaminated mangrove soil with optimal conditions of 30% and 15% concentration, 1:5 soil-liquid ratio, and pH 2. The removal efficiency of Ni ions was 70.8% and 70.0% for ChCl-LevA and ChCl-AceA, respectively. XRD of different mangrove soil samples and FTIR of DESs solution were investigated to provide in-depth knowledge for the mechanism and kinetics studies. Soil minerals did not undertake significant mineralogical deviations or corrosion when washed with DES. The interaction of DESs with metal ions was confirmed by the dominant peak in washed DES solution only and not in fresh DESs, verifying the binding of metal ions after washing with DES. This study investigated and reported the reaction kinetics and mechanism between DES and heavy metals (lead, arsenic and nickel). The experimental and modeling results were discovered to be in good agreement. It is deduced that the washing process fitted with the Lagergren pseudosecond- order kinetic model concerning both DES for all metal ions studied. The model’s maximum Pb2+ dissolution capacity, Qe, is 0.03331 mg g-1 and 0.25298 mg g-1 of ChCl- LevA and ChCl-LacA, respectively. The model’s maximum AsO₄³⁻, + dissolution capacity, Qe are 0.00545 mg g-1 1 of TBAC: TEG. The model’s maximum Ni dissolution capacity, Qe, is 51.56 mg g-1 and 52.00 mg g-1 of ChCl-LevA and ChCl-AceA, respectively. Overall, green and natural DESs offer an environmentally sustainable alternative as a washing solution. Soil washing to remove heavy metals is a simple, quick, and low-cost remediation process that could potentially be utilized to reduce soil contamination.